Pulmonary nodules measurements in CT lung cancer screening - Heuvelmans, Marjolein A.; Oudkerk, Matthijs (Journal of Thoracic Disease, 2018)
To decrease the number of false-positive screen results without losing sensitivity for lung cancer diagnosis, accurate lung nodule management is crucial in low-dose CT lung cancer screening.